Ethnobotanical knowledge of plant species of the North-East of Morocco, with three provinces as a case study: Al Hoceima, Nador, and Jerada. - Mir, Fatima-Zahra; Smaili, Halima; Merzouki, Abderrahmane (Mediterranean Botany, 2024)
This study focuses on taxa found in the Northeastern part of Morocco and cited in the book “Al Jam’ li-Mufradat al-Adwiya wa’l-Aghdiya (The Book of Simple Drugs) by Ibn Al Baytar. The main objective of this study is to determine whether the taxa on our list are recognized by the populations in the three provinces of Northeastern Morocco, as well as to collect information about their traditional uses (medicinal or non-medicinal), their modes of preparation and administration, the plant parts used. All the data have been collected through conducting an open-ended, semi-structured interviews with randomly selected individuals. The informant consensus factor (FIC) was calculated to identify the level of agreement among informants regarding the use of medicinal plants for specific disease groups. During these ethnobotanical surveys, 1,177 persons were interviewed. We were able to record a total of 241 taxa belonging to 66 families with 1,264 uses mentioned in the three provinces. The results obtained confront us with the idea that there is a decline of autochthonous knowledge. They reveal that 32.12% of the local population considers itself ignorant of the uses of plants to cure illness, and that 66.78% prefer modern medicine despite possessing some knowledge of traditional medicinal plants. However, 790 medicinal uses recorded were classified according to the WHO’s international Classification of diseases (ICPC-2, International Classification of Primary Care), and 474 other uses were recorded, along with the transcription of new vernacular names for 107 taxa. This confirms the importance of ethnobotanical studies as it plays an important role in preserving the reservoir of indigenous knowledge from being lost over time.